Descriptors for quinoa (Chenopodium quinoa Willd) and wild relatives - Bioversity International; Fundación para la Promoción e Investigación de Productos Andinos; Instituto Nacional de Innovación Agropecuaria y Forestal; International Fund for Agricultural Development; Food and Agriculture Organization of the United Nations (Bioversity International, 2013)
Descriptors for quinoa (Chenopodium quinoa Willd.) and its wild relatives, is a revision of the original IBPGR (now Bioversity International) publication titled ‘Descriptores de quinua’ (AGP:IBPGR/81/104). This revision, expanded to accommodate wild relatives, is the result of a joint collaboration effort involving Bioversity International, FAO, PROINPA, INIAF and IFAD. During the review process, more than 50 quinoa scientists from 11 countries and different organizations provided their expert advice.